Analysis of Indonesian Naval Ship Maintenance Strategy at Jakarta Military Sea Lift Unit to Support Sea Transportation - Mei Edi Prayitno; Aries Sudiarso; Dohar Sianturi (International Journal of Marine Engineering Innovation and Research, 2021)
The background of the research is the limited readiness of ships at the Jakarta Military Sea Lift Unit caused by the age of most of the ships more than 20 years. The purpose of the study was to analyze the strategy of maintaining ship readiness through system maintenance activities. The research method is quantitative with a survey approach with an analysis model based on Strength, Weakness, Opportunity, and Threat (SWOT). Research respondents are purposive sampling that have relevance in the field of ship maintenance. The results showed that to improve ship readiness through maintenance systems, was carried out by increasing the capabilities of human resources, Management Planned maintenance systems, The availability of spare parts, and the capability of the Ship Maintenance Facility Unit. The improvement of personnel capabilities and skills is carried out through training activities in collaboration with the original engine manufacturer (OEM). This ship maintenance system is based on a planned maintenance system supported by the availability of spare parts and the capability of Ship Maintenance Facility Units. Contribution of the research to maintain the readiness of ships to support operational activities, which has implications for the readiness and sustainability.